The effect of consistent and specialized freestyle wrestling training on muscle synergy during the double-leg attack technique: A comparison between elite and sub-elite wrestlers - Beinabaji, H.; Eslami, M.; Hosseininejad, S. E.; Afrakoti, I. E. P. (Journal of Advanced Sport Technology, 2025)
Introduction: Freestyle wrestling requires precise and coordinated movement execution, with the Double-Leg Attack technique playing a crucial role in gaining advantage. Understanding the underlying mechanisms and effects of specialized wrestling training is essential for optimizing performance. Muscle synergy or modular control of movement involve coordinated patterns of muscle activation and the organization of muscles into functional units or modules. Exploring these concepts in freestyle wrestling can provide insights into optimizing movement coordination and performance outcomes by studying the synergistic interaction of different muscles.